Elections in Japan, Korea, and Taiwan under the single non-transferable vote : the comparative study of an embedded institution - Grofman, Bernard (Book collections on Project MUSE., 1999)
"Through comparative studies of the adoption and rejection of SNTV and the consequences of its use in various settings, the contributors explore the differences in the operation and the effects of the application of one rule in three different countries. Arguing that any single feature of a political system is embedded in a political structure and cannot be understood without studying its relationship with other parts of the political system, the authors demonstrate how the same rule can have different consequences depending on the context in which it operates."--Jacket.